Implementasi Model Pembelajaran GI (Group Investigation) untuk Meningkatkan Hasil Belajar IPA Tema 9 “Menjelajah Angkasa Luar” bagi Siswa Kelas VI SD Negeri Tlogosari Kulon 03 Semarang - Rubiyati Rubiyati (Jurnal Inovasi Pembelajaran di Sekolah, 2023)
Based on the background of the problems described above, several problems can be identified as follows: students who are less able to master science learning in class VI even semester at SD Negeri Tlogosari Kulon 03. Out of 39 children, only 14 children (35.90%) achieved the KKM. The teacher's efforts to improve the ability of science learning outcomes Theme 9 "Exploring Outer Space" by using GI (Group Investigation) in grade VI even semester students of SD Negeri Tlogosari Kulon 03 Semarang. This study used the type of PTK (classroom action research), conducted at Tlogosari Kulon 03 Public Elementary School, Pedurungan District, Semarang City in February–April 2022. The subjects of this classroom action research were: Class VI students, totaling 39 students. The results of the study showed: (1) Learning by using GI (Group Investigation) can improve student learning outcomes in Theme 9 "Exploring Outer Space" in Science class VI at SD Negeri Tlogosari Kulon 03 Kec. Pedurungan Semarang City which is characterized by an increase in student learning outcomes in each cycle, namely pracycle 64.41; cycle I average 71.90 and cycle II average 79.90; (2) Learning by using GI (Group Investigation) can improve the completeness of student learning outcomes in Theme 9 "Exploring Outer Space" in Class VI Science class at SD Negeri Tlogosari Kulon 03 Kec. Pedurungan Semarang City which is characterized by an increase in student learning outcomes in each cycle, namely pre-cycle 35.90%; in cycle I increased to 69.23% and cycle II reached 84.62%. The conclusion of this study is that the learning outcomes and mastery of student learning in science lessons on Theme 9 "Exploring Outer Space" can increase the application of GI (Group Investigation) students in class VI Semester 2 SD Negeri Tlogosari Kulon 03 Pedurungan District, Semarang City, Academic Year 2021/2022.